Dampak Destinasi wisata edukasi Kampung Bahasa Mandarin pada Peningkatan Ekonomi Warga di Dusun Tumpuk Desa Besuki Kecamatan Besuki Kabupaten Tulungagung - Junari Junari (Pusat Riset dan Inovasi Nasional, 2026)
The objective of this study is to examine the impact of the Mandarin Language Village educational tourism destination on the economic improvement of residents in Tumpuk Hamlet, Besuki Village, Besuki District, Tulungagung Regency. This field research employs a qualitative, descriptive case study approach, with data collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings show that the Mandarin Language Village has generated significant positive effects on the community’s economic and social conditions by creating new business opportunities, providing employment for local residents—including former migrant workers—and stimulating the village’s economic activity. Moreover, the collaboration between Ma Chung University Malang, the Supreme Council of GKJW, and the village government demonstrates an effective partnership model for education-based rural development and community empowerment. Despite challenges such as limited human resources and infrastructure, the Mandarin Language Village has proven to be a sustainable educational tourism model that contributes meaningfully to the welfare and self-reliance of rural communities.